2011
DOI: 10.1128/jvi.02217-10
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Fitness Landscape of an RNA Virus by Using a Universal Barcode Microarray

Abstract: Studies of viral pathogenesis have relied heavily on analyses of specific clones and their genetic determinants of virulence. It is sometimes difficult to apply this reductionist approach to the study of RNA viruses, which by virtue of their very high mutation rates, exist as a complex mixture of mutants. While quasispecies theory has provided an intellectual framework for exploring the relationship between the viral population structure and phenotype, experimental studies have been limited by the relatively p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 65 publications
1
37
0
Order By: Relevance
“…The results confirm the depth of mutant spectra in RNA virus populations in general, previously uncovered using standard molecular and biological cloning, followed by Sanger sequencing, and further evidenced by the recent application of ultradeep sequencing, microarray analysis, or successive amplification methods (13,18,27,41,45,57,(76)(77)(78).…”
Section: Discussionsupporting
confidence: 70%
“…The results confirm the depth of mutant spectra in RNA virus populations in general, previously uncovered using standard molecular and biological cloning, followed by Sanger sequencing, and further evidenced by the recent application of ultradeep sequencing, microarray analysis, or successive amplification methods (13,18,27,41,45,57,(76)(77)(78).…”
Section: Discussionsupporting
confidence: 70%
“…This difference led John J. Holland and colleagues to emphasize in a seminal paper a number of disease implications of a rapidly evolving RNA world immersed in a far more static cellular DNA world (Holland et al , 1982). Most predictions of Holland and colleagues have been confirmed by findings made in the following decades that have linked rapid RNA genome evolution with RNA viral disease mechanisms [reviewed in (Domingo et al, 2012; Lauring and Andino, 2011)]. Since the size of RNA viral genomes lies between 3 Kb and 33 Kb, close to the inverse of the mutation rate, it is thought that it is unlikely to produce progeny RNAs identical to the parental genome even within the confined limits of a single replicative unit (each one of the replication complexes) within a single infected cell.…”
Section: Formation Of Mutant Spectra and Origin Of Internal Interactionsmentioning
confidence: 89%
“…Repeated artificial bottlenecks in viral populations have been demonstrated to severely restrict viral fitness (Duarte et al, 1992), and natural bottlenecks have been observed during a wide variety of virus transmission and dissemination events, including: human immunodeficiency virus, Venezuelan equine encephalitis virus, polio virus, hepatitis C virus, and various plant viruses (Derdeyn et al, 2004; Forrester et al, 2012; Wang et al, 2010). Furthermore, studies have utilized genetic tags to track polio and VEEV populations during these events (Forrester et al, 2012; Lauring and Andino, 2011; Pfeiffer and Kirkegaard, 2006). Here we present an approach to experimentally track IAV transmission through the addition of genetically neutral barcodes to the viral genome.…”
Section: Introductionmentioning
confidence: 99%